An Overview of the Teamwork between Paramedics, Nurses, and Dentists in Treating Facial Injuries in Emergency Settings - Ali Abdullah Saeed Alasmary; Adel Ibrahim Abdullah aljohani; Amna Hisham Musbah; Ghadeer Saeed Alzain; Entesar Mahdi Almahdod; Nawal Hamdan AL jadani; Hadeel Eshaq Shazly (International Journal of Medical Toxicology and Legal Medicine, 2024)
Facial injuries constitute a significant portion of trauma cases encountered in emergency medical settings, necessitating a coordinated, multidisciplinary approach to care. This overview examines the critical roles played by paramedics, nurses, and dentists in the management of facial trauma, highlighting how their collaborative efforts contribute to enhanced patient outcomes. Paramedics initiate care in pre-hospital settings, focusing on rapid assessment and stabilization of life-threatening injuries, particularly airway management, which is vital in cases of facial trauma. Once patients reach emergency departments, nurses conduct comprehensive evaluations, administer treatment protocols, and educate patients about their injuries and recovery processes. Dentists, particularly those specializing in oral and maxillofacial surgery, are essential for evaluating and treating injuries involving dental structures and facial bones, employing advanced diagnostic tools and surgical techniques. The success of managing facial injuries depends significantly on effective communication and teamwork among these professionals, which is facilitated through interdisciplinary collaboration and established workflow protocols. Engaging collaboratively enhances the efficiency of care delivery, minimizes delays in treatment, and fosters a patient-centered approach that addresses both immediate medical needs and long-term recovery. The overview underscores the significance of integrated healthcare delivery models, advocating for ongoing training and protocol development to strengthen collaborative practices in emergency settings. Ultimately, promoting teamwork among paramedics, nurses, and dentists leads to improved health outcomes for patients facing complex facial injuries, reinforcing the importance of a holistic and collaborative approach in trauma care.